Women and Poverty - Laguilles, Rowena; Ofreneo, Rosalinda Pineda; Hega, Mylene; Buenaventura, Mae; Manglinong, Zeena; Riego, Rianne; Narito, Zonia (Review of Women's Studies; Vol 25 No 1-2 (2015): Review of Women's Studies Volume XXV, Numbers 1-2 (January-December 2015), 2018)
Strategic Objectives: A1. Review, adopt and maintain macroeconomic policies and development strategies that address the needs and efforts of women in poverty A2. Revise laws and administrative practices to ensure women ís equal rights and access to economic resources A3. Provide women with access to savings and credit mechanisms and institutions A4. Develop gender-based methodologies and conduct research to address the feminization of poverty (BPA 1995)